La Palestine comme écran, ou comment passer « de l’autre côté du miroir » - Laure Fourest (Revue des Mondes Musulmans et de la Méditerranée)
The uncertainty undermining the term «Palestine », caused partly by the loss of its geographical referent since the creation of the State of Israel, has fostered a great variety of competing representations which have turned this term into a screen of sorts. The latter reveals the complexity of the geopolitical interests involved in the conflict, but makes it extremely difficult for Palestinians to articulate their own narratives and representations. Working on Palestinian film production amounts to exploring how filmmakers deal with the numerous representations of their land and people such as they are produced by Others, whether Israelis or Westerners. Our study is based on one of the most convincing creations in this production; in Port of Memory [2009], Kamal Aljafari uses sequences taken from Israeli and Hollywood films shot in Jaffa in the 1970s and 1980s where Palestinian inhabitants were excluded. To deal with such mutilated representations of the place, he uses cinematic language to correct the images and invest the visual memory of Others with his artistic and political expression.